Three-dimensional X-ray microcomputed tomography of carbonates and biofilm on operated cathode in single chamber microbial fuel cell - Santini, Maurizio (2018)
Power output limitation is one of the main concerns that need to be addressed for full-scale applications of the microbial fuel cell technology. Fouling and biofilm growth on the cathode of single chamber microbial fuel cells (SCMFC) affects their performance in long-term operation with wastewater. In this study, the authors report the power output and cathode polarization curves of a membraneless SCMFC, fed with raw primary wastewater and sodium acetate for over 6 months. At the end of the experiment, the whole cathode surface is analyzed through X-ray microcomputed tomography (microCT), scanning electron microscopy, and energy-dispersive X-ray spectroscopy (EDX) to characterize the fouling layer and the biofilm. EDX shows the distribution of Ca, Na, K, P, S, and other elements on the two faces of the cathode. Na-carbonates and Ca-carbonates are predominant on the air (outer) side and the water (inner) side, respectively. The three-dimensional reconstruction by X-ray microCT shows biofilm spots unevenly distributed above the Ca-carbonate layer on the inner (water) side of the cathode. These results indicate that carbonates layer, rather than biofilm, might lower the oxygen reduction reaction rate at the cathode during long-term SCMFC operation.